(untitled) (International Journal of Physiotherapy, 2019)
Introduction: Atrophy of the diaphragm muscle has been reported after no more than 18 hours on mechanical ventilation. Inspiratory muscle training and spontaneous breathing trials can be seen as intrusive weaning. We, therefore, hypothesized that endurance training of the diaphragm muscle by systematically reducing pressure support would prepare the patient for weaning. Method: Adult critically ill patients, mechanically ventilated for more than 24 hours and expected intubated for more than 48 hours in the ICU of Odense University Hospital were enrolled. Demographic data, blood gas, and respiratory function parameters were among the data recorded at the beginning, during and after the training session. A physiotherapist led the intervention and during training, pressure support was reduced with a maximum of 50%. Results: 20 patients were enrolled. The mean APACHE II score was 21.7. Before training, the pressure support level was 8.5 (5-10) H2O. 120 minutes after training, the median value remained lower than 7 (5-10) H2O. The RASS level during the training was 0 (0 to -1). After three days, 16 out of the 20 (80%) patients were successfully extubated and after five days, additionally, two patients were extubated. During the intervention period, two patients died of other causes. Conclusion: A physiotherapist driven training program is both safe and feasible and could identify patients ready to wean. Reduction in pressure support levels obtained during training could be maintained afterward.